Challenges in the postsurgical recovery of cushing syndrome: glucocorticoid withdrawal syndrome - Zhang, Catherine D.; Ioachimescu, Adriana G. (Frontiers in Endocrinology, 2024)
Glucocorticoid withdrawal syndrome is a challenging clinical phenomenon that can complicate the postsurgical recovery of Cushing syndrome. It is characterized by physical tolerance and dependence to supraphysiologic glucocorticoid exposure during active Cushing syndrome followed by the abrupt decline in cortisol levels after surgical treatment. The symptoms of glucocorticoid withdrawal often overlap with those of postoperative adrenal insufficiency and can be difficult for patients to cope with and for clinicians to treat. This mini review will discuss the clinical characteristics, pathophysiology, and management of glucocorticoid withdrawal syndrome while highlighting recent data in the field.